The Development of Transmigration in Indonesia - Malta (Global Writing Academica Researching & Publishing, 2023)
Transmigration development is an effort to bring together human resources and natural resources through population movement and space utilization. The implementation of transmigration is a long-term process within the framework of creating a productive, advanced, and independent community in a harmonious, dynamic, and prosperous life. The implementation of transmigration is a system for developing regions through a process of structuring population distribution as well as regional development with the ultimate goal of achieving the welfare of transmigrants and the surrounding community. The implementation of transmigration has the potential to contribute in overcoming some of the national problems, including continuing regional development, increasing food production, expanding job opportunities, and business opportunities for the economically weak and alleviating poverty.